Factors affecting in total milk yield and lactation period in Cyprus , Local goats and their cross - مهدي العزاوي, زيد محمد; ابراهيم سعيد, سعد; ندا, سعد محمد (Journal of Kerbala for Agricultural Sciences, 2015)
This study was carried out in the station for ruminant research of the State Board for Agriculture Research, Ministry of Agricultural in Abu Ghraib (23 km west of Baghdad) for the period of 1/10/2012 - 25/9/2013. The objective of the present study was to study of effect factors in total milk yield (TMY) and lactation period (LP( in Cyprus , Local goats and their cross. The study included 607 records for TMY and LP of 163 goats. The overall means for total milk yield through 179.54 days was 180.88 kg. The least squares means for milk yield 221.31 ± 6.40 , 149.84 ± 8.54 and 171.51 ± 11.21 kg in Cyprus , Local goats and their cross , respectively and lactation period were 172.51± 2.12 , 188.46 ± 2.90 and 177.67 ± 3.62 days in Cyprus , Local goats and their cross , respectively. Genetic groups and production year were highly significant (P<0.01) on TMY and LP ,but type of birth and sex of kid were non- significant. Age of goat was highly significant (P<0.01) on LP. regression of TMYon LP and LP on TMY were highly significant (p< 0.01). Key words : total milk yield , Cyprus . Local , goats